Alterations and Dynamics of Major Meningitis Etiological Agents During and Post-COVID-19 Pandemic: A Systematic Review - Luís Arthur Brasil Gadelha Farias; Larissa Santos Weyne; Lenifer Siqueira Landim; Pablo Eliack Linhares de Holanda; Aliniana da Silva Santos; Luciano Pamplona de Góes Cavalcanti; Lourrany Borges Costa; Antonio Gutierry Neves Dantas de Melo; Melissa Soares Medeiros; Evelyne Santana Girão; Tânia Mara Silva Coelho; Lauro Vieira Perdigão Neto (Tropical Medicine and Infectious Disease)
The transmission dynamics of many pathogens were altered during the coronavirus disease 2019 (COVID-19) pandemic. Several factors, including control measures and social distancing, have influenced the circulation and epidemiology of major etiological agents of meningitis during this period. This review examined trends in the primary etiologic agents of meningitis during and after the COVID-19 pandemic. A comprehensive literature search was conducted using the MEDLINE, Embase, LILACS, and SciELO databases for studies published between 2020 and 2024. The data were summarized descriptively and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Thirty-eight studies are included in this review. Bacterial and viral meningitis pathogens exhibited significant epidemiological shifts during the pandemic. A marked decline in infections caused by the enteroviruses, Neisseria meningitidis, Streptococcus pneumoniae, and Haemophilus influenzae was observed from 2020 to 2021 in the northern and southern hemispheres during the pandemic. Post-pandemic, meningitis cases increased, with a resurgence in various countries. Despite the heterogeneity of the studies, the evidence indicates that the COVID-19 pandemic significantly affected the epidemiology of meningitis-causing microorganisms during and after the pandemic. Understanding these epidemiological shifts and dynamics is crucial for defining the control measures, vaccination strategies, and public health policies in the post-COVID-19 era.